Pengelolaan Dana Desa, Akuntabilitas Dan Partisipasi Masyarakat Terhadap Pembangunan Desa Guwokajen, Sawit, Kabupaten Boyolali - Ferta Solidahwati; Darmanto Darmanto; Yuwita Ariessa Pravasanti (Jurnal Ilmiah Keuangan Akuntansi Bisnis (JIKAB), 2023)
This study aims to determine Village Fund Management, Accountability and Community Participation in Village Development in Guwokajen Village, Sawit District, Boyolali Regency. The data used is primary data. Data analysis methods, Descriptive Statistical Test, Validity Test, Reliability Test and Classical Assumption Test. Classical Assumption Test consists of normality test, multicollinearity test and heteroscedasticity test. Hypothesis testing using multiple linear regression F test, t test and R2 based on the results of research that has been carried out on all data obtained in Guwokajen Village, it is concluded that Village Fund Management accountability and community participation have a positive and significant influence on village development. Village Fund Management, Accountability and Community Participation simultaneously have a positive effect on the amount of development in Guwokajen village. Keywords: Village fund management, accountability, community participation and village development